Two new species of Larsia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae) from Neotropical Region, with a checklist of Larsia species of the world - de Oliveira, Caroline Silva Neubern; Da Silva, Fabio Laurindo (Zootaxa, 2011)
Two new species of Larsia Fittkau, 1962 are described and figured as male, pupa and larva. Diagnosis to male of this genus is emended. An annotated checklist of the world’s valid Larsia species is given and keys to pupae and larvae of known species in the Neotropical region are provided.